PENGARUH KEPEMIMPINAN DAN KOMPENSASI DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA KARYAWAN PT. 1st KAYATA MAKMUR SEJAHTERA MAKASSAR - Ilham AR Ilham AR; Isman Isman (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims to determine the influence of leadership and compensation with motivation as an intervening variable on employee performance. This research was conducted at PT. 1st Kayata Makmur Sejahtera, Makassar. The sample used is 37 people. Hypothesis testing is done by linear regression analysis for hypothesis 1, 2, 3, 4 and 5 through SPSS program ..for windows while for hypothesis 6 and 7 using path analysis and test of sobel. The method of analysis used in this research is comparative causal with quantitative approach. The data testing techniques used include the validity, reability, classical assumption and the test of the sobel to test the mediation effect. Data collection used is the distribution of questionnaires, interviews and documentation. Based on the results of research analysis with the level shows that there is a significant positive influence of leadership variables on motivation. There is a significant positive influence of the compensation variable on motivation. There is a significant positive influence of the motivation variable on performance. There is a significant positive influence of leadership variables on performance. This is evidenced by the value of significance on the variable compensation on performance. There is a significant positive influence of the compensation variable on performance. There is a significant positive indirect effect of leadership variable on performance through motivation variable. There is a significant positive indirect effect of leadership variable on performance through motivation variable.